2016
DOI: 10.35248/2684-1304.16.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Study of Skeletal Remains: Solving a Homicide Case with Forensic Anthropology and Review of the Literature

Abstract: The present study examines a case in which signs of incised wounds were found on skeletal remains of a murder victim. The authors have studied the skeletal remains and the dynamics of the murder in order to reconstruct the kind of weapon utilized. The bones examined belonged to a woman that had disappeared from almost 10 years and where recovered from the garden of the house belonging to her former partner. The main feature of these remains was the discovery of a damage of a thoracic vertebra (T1). Our examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Further, collections of high-resolution post-mortem and clinical CT databases eliminates the need for bone preparation, the deterioration of physical samples over time, and allows for easy data sharing and distribution for rapid analysis [ 28 , 44 ]. The virtual nature of CT and its associated imaging modalities allows access where physical examination is impossible [ 45 , 46 ]. The virtual access also provides users with the opportunity to engage in transnational research and analysis, with virtual reconstructions being analysed between institutions in different geolocations [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, collections of high-resolution post-mortem and clinical CT databases eliminates the need for bone preparation, the deterioration of physical samples over time, and allows for easy data sharing and distribution for rapid analysis [ 28 , 44 ]. The virtual nature of CT and its associated imaging modalities allows access where physical examination is impossible [ 45 , 46 ]. The virtual access also provides users with the opportunity to engage in transnational research and analysis, with virtual reconstructions being analysed between institutions in different geolocations [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is typically done through the conversion of DICOM data into a surface model, an STL (stereolithography) file. With the success of machine learning techniques in analysing nonmedical images [ 51 ], there is currently a rise in number of studies which utilise machine learning (ML) and artificial intelligence on biological profile estimations in FA [ 14 , 16 , 17 , 46 , 52 , 53 , [53] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ]. ML studies in medicine and FA have shown that 3D image files restructured from DICOM images such as Neuroimaging Informatics Technology Initiative (NIfTI), Wavefront Alias (OBJ), and STL is gaining interest and may be a valuable file format for convolutional neural networks in processing volumetric data [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…Öldükten uzun zaman sonra ve/veya çevresel faktörlere bağlı olarak cesetler, yumuşak doku ve iç organları çürümüş, yanmış, mumyalaşmış, sabunlaşmış, iskeletleşmeye yüz tutmuş veya tamamen iskeletleşmiş durumda bulunabilmektedir. Bu tür vakalarda adli antropoloji bilimi metot ve teknikleri kullanılarak teşhis edilemez ve otopsi yapılamaz hale gelmiş cesetlerin biyolojik profilleri (yaş, boy, cinsiyet, etnik köken), dental özellikleri, yaşa veya hastalığa bağlı kemiklerde gözlemlenen patolojik durumları, ölüm sonrasına ait tafonomik sebeplerden meydana gelmiş değişikliklerle birlikte, ölüm zamanına ait travmalar incelenerek muhtemel ölüm nedenleri belirlenebilmektedir (5)(6)(7)(8)(9)(10)(11)(12)(13). İnsan iskeletlerinde ölüm zamanına ait travmalar, kemiklerde tespit edilen kırık, çizik/kesik, yarık, delik, çökme ve deformasyonların analizleri ile mümkün olabilmektedir.…”
Section: Introductionunclassified